Pengembangan Aplikasi Pengelolaan Obat Melalui Metode Fifo Dan Fefo Di Instalasi Farmasi Rsud Prof.Dr.H.M. Anwar Makkatutu Kabupaten Bantaeng - Darma Suhesti; Amir Imbaruddin; Nuraeni Suyuti (Universitas Kristen Indonesia Toraja, 2023)
The main problem in this research is the management of drugs in the Pharmacy Installation of RSUD Prof. Dr. H. M. Anwar Makkatutu which has not been handled properly. There are various types of pharmaceutical logistics, namely drugs and consumables, many types of incoming drugs and medical equipment, with different delivery times and drug expiration dates, the pharmacy must manage it well, starting from the process of distributing and storing drugs and consumables. from warehouse to depot. The pharmaceutical system that is still manual causes repeated double checks, the data collection of expired drugs is not correct, there is no application that makes it easy for pharmacy officers to check what drugs are about to expire and are about to expire so that it requires a long time and excessive energy. With the above problems, the development of drug management applications through the fifo and fefo methods in SIMRS when receiving, storing and releasing drugs and medical equipment is needed for smooth service in pharmaceutical installations so that officers can work effectively, efficiently, and improve service quality. as well as the economic disadvantages of hospital management can be minimized and produce reports that are faster and more accurate in the management and planning of drug supplies. Pharmacy officers can take advantage of drug management through the fifo and fefo applications based on batch numbers and expiration dates to complete all the shortcomings and weaknesses of the existing SIMRS application in order to maximize services at the Pharmacy Installation. This research is a quasi experimental research to determine the difference in the duration of the use of time and energy before and after using the application. The research was carried out at the pharmacy installation of Prof. Dr. H. M. Hospital. Anwar Makkatutu Bantaeng from August to October 2020.